Efektivitas Metode Pekerjaan Pelat Lantai Bondek, Half Precast dan Konvensional Gedung Asrama Putra Al-Azhar - Muhammad Romadhoni; Muh. Nur Sahid (Kadiri University, 2023)
The floor plate is one of the important components in a multi-story building. Conventional methods are still widely used for building floor slabs. This method requires a lot of labor and time, which can reduce productivity. Other methods, such as bondek and half precast in floor slab work, are expected to increase work effectiveness and efficiency. This study aims to determine which method is most effective in floor slab work by reviewing cost, time, and work productivity. Floor plate planning consists of calculating each method's structural strength and volume of work, including formwork, reinforcement, concrete, and formwork dismantling. Cost analysis is carried out by collecting data on material prices and labor wages for the building's Draft Budget (RAB). Estimated work time involves formwork preparation, installation of reinforcement, and concrete casting for the three work methods. Based on the results of the calculation analysis on the floor slab work of the Al-Azhar Boys Dormitory Building with an area of the floor plate of 375,318 m2. Conventional floor slab work is more economical than bondek slab work by around 31.23%, but requires the longest work time. Meanwhile bondek floor slabs offer the fastest processing time, even though the cost is higher than conventional slabs, around 31.19% and 5.18% lower than half precast slabs. This can be a recommendation in choosing a floor slab work method.